Measurement of Supply Chain Performance by Using Supply Chain Operation Reference Based on Analytical Hierarchy Process: Pengukuran Kinerja Rantai Pasok dengan Menggunakan Supply Chain Operation Reference Berbasis Analytical Hierarchy Process - Mursyid, Muhammad Saadillah; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2019)
This study uses the Supply Chain Operation Reference (SCOR) and Analytical Hierarchy Process(AHP) methods. From the result of research using Supply Chain Operation Reference (SCOR) method and Analytical Hierarchy Process (AHP) produced 27 KPI where for plan perspective there are 4 KPI consisting of reliability 2 KPI, responsiveness 2 KPI. For a source perspective there are 8 KPI consisting of reliability 4 KPI, responsiveness 2 KPI, Flexibility 2 KPI. Make perspective there are 7 KPI consisting of reliability 3 KPI, responsiveness 2 KPI, flexibility 2 KPI. For a delivery perspective there are 5 KPIs that consist of 3 KPI reliability, 2 KPI responsiveness. Then for the return perspective there are 4 KPI consisting of 2 KPI reliability, 2 KPI responsiveness. Then with the Analytical Hierarchy Process (AHP) method produced a delivery perspective is the perspective with the highest level of importance on the supply chain performance of PT. MSM. With the results of this performance measurement can be used as a benchmark for the company to get optimal performance.